Caracterização do efluente de laticínio: análise e proposta de tratamento - Henares, Juliana Ferreira (2015)
Industries are mainly responsible for water contamination, as the effluents are released to water courses without proper treatment, or disposed of improperly in the soil; can cause serious damage to the environment, contaminating soil, surface and groundwater, making it unfit for use and also generating health problems to humans. The main environmental impacts of dairy industries are related to the release of wastewater, since they are generated 1-6 liters of sewage per liter of processed milk. Thus, the release of wastewater in receiving waters should be subject to limits set according to the conditions of water quality, as their class effluent discharge standards. In Paraná, Resolution regulating the release limit is the number 430, of May 13, 2011 the National Environmental Council. Thus, this study aims to characterize the liquid discharges generated by Dairy Paradise Resort, the city of ManoelRibas, Parana; and present possible ways of treating their effluents, adjusting them according to the law. For this, it was necessary site visits to interview with the responsible for the production, to know what are the process steps that generate more waste and which products are used in these procedures; It analyzed the physical-chemical characteristics of the effluent where biological treatment viability was detected, since the COD / BOD5 ratio was between 2.5 and 3.5. Also analyzed the flow of wastewater daily, resulting in a volume ratio of liquid effluent equal to 5,5, and precise management actions to reduce this coefficient to be between 0.5 and 2.0 liters effluent / liters milk. To take advantage of the existing lagoons on site, the wastewater treatment system will be stabilization ponds.